2022
DOI: 10.3390/antibiotics11091170
|View full text |Cite
|
Sign up to set email alerts
|

WGS-Based Lineage and Antimicrobial Resistance Pattern of Salmonella Typhimurium Isolated during 2000–2017 in Peru

Abstract: Salmonella Typhimurium is associated with foodborne diseases worldwide, including in Peru, and its emerging antibiotic resistance (AMR) is now a global public health problem. Therefore, country-specific monitoring of the AMR emergence is vital to control this pathogen, and in these aspects, whole genome sequence (WGS)—based approaches are better than gene-based analyses. Here, we performed the antimicrobial susceptibility test for ten widely used antibiotics and WGS-based various analyses of 90 S. Typhimurium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 97 publications
1
13
0
Order By: Relevance
“…We found 26 chromosomal genes in all the SG strains, with most encoding efflux pumps, associated with resistance to 16 classes of antimicrobial agents as well as antiseptics and disinfectants. These results are similar to previous WGS-based studies of chromosome-encoded genes [ 49 , 50 , 51 ]. The bacterial chromosome-encoded systems involved in AMR typically confer a low level of resistance, but they are important as possible ‘stepping stones’ to higher levels of resistance [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found 26 chromosomal genes in all the SG strains, with most encoding efflux pumps, associated with resistance to 16 classes of antimicrobial agents as well as antiseptics and disinfectants. These results are similar to previous WGS-based studies of chromosome-encoded genes [ 49 , 50 , 51 ]. The bacterial chromosome-encoded systems involved in AMR typically confer a low level of resistance, but they are important as possible ‘stepping stones’ to higher levels of resistance [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…One gene, aac(6')-Iaa, which confers resistance to aminoglycosides, was detected in the chromosome of all Salmonella subspecies diarizonae (3) and enterica (165) but not in arizonae (3) (Fig 1). The frequency of Salmonella enterica subspecies enterica isolates that carried an aminoglycoside acetyltransferase aac(6')-Iaa has been reported to be high (>95%) in multiple WGS analysis [55][56][57]. However, in a surveillance study of non-typhoidal Salmonella enterica, 11 isolates out of 3,491 (0.3%) showed phenotypic resistance to an aminoglycoside antimicrobial [55].…”
Section: Antimicrobial Resistance Profilementioning
confidence: 99%
“…In a similar study on Salmonella from small ruminants in Peru, partial concordance between the genotype and phenotype was identified. However, investigators also found some AMR was not predicted by the genotype [ 31 ]. A global study of AMR in Salmonella typhoid also found a similar result [ 28 ], suggesting that phenotype determined by MIC is not only conferred by known genes and may include yet-to-be-discovered regulatory methods.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AMR gene presence to predict resistance phenotype has not been widely validated in multiple bacteria and within a genus [ 28 ]. Genotype predictions of phenotype are emerging with variable results; even within a single organism, the concordance of AMR genotype with phenotypic is variable [ 31 , 32 , 33 ]. Studies in Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation